Talking to Your Teens About Dating - Kate Fogarty; Donna Davis (EDIS)
“Talking to teenagers about dating may seem like a daunting task to some parents who are thinking their teen will assume the 'Oh no, not another parent talk again' posture. You know the one—head cocked, eyes rolled, and arms crossed. However, talking about it can be very important in determining how your teen approaches dating and his or her future relationships.” This 2-page Family Album Radio transcript was written by Kate Fogarty and Donna Davis, and published by the UF Department of Family, Youth and Community Sciences, July 2012.